1982
DOI: 10.2134/agronj1982.00021962007400060033x
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Deficiency and Toxicity in Wheat: Influence on Growth and Forage Quality of Herbage1

Abstract: There is little information concerning critical Mn deficiency and toxicity levels in forage plants, or how plant Mn concentration affects other plant constituents associated with forage quality. This study was undertaken to investigate possible interactions between plant Mn concentration and the growth and forage quality of wheat (Triticum aestivum L. cv. Stacy). Wheat plants were grown in nutrient solution containing 0.005, 0.02, 0.05, 0.25, 1, 5, 25, 100, 200, and 500 µg/g Mn. Plants were grown for 30 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
0
8
1
Order By: Relevance
“…The lower Mn concentrations in the PLA treatments may have been due to the higher pH of the PLA (Table 1). These tissue Mn levels are near or exceed the phytotoxic threshold levels of 475 mg Mn kg −1 reported by Fales and Ohki (1982) Copper and Mn concentrations increased with lime treatment while Fe, Ni, and Cd concentrations were reduced (Table 7)…”
Section: Resultsmentioning
confidence: 57%
“…The lower Mn concentrations in the PLA treatments may have been due to the higher pH of the PLA (Table 1). These tissue Mn levels are near or exceed the phytotoxic threshold levels of 475 mg Mn kg −1 reported by Fales and Ohki (1982) Copper and Mn concentrations increased with lime treatment while Fe, Ni, and Cd concentrations were reduced (Table 7)…”
Section: Resultsmentioning
confidence: 57%
“…The use of Stacy wheat was based on two primary reasons. This cultivar has been adapted to the Experiment, GA region and is commonly grown with high yields (1), and several studies (6,23,24) on Stacy have reported critical Mn deficiency levels for growth and physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, even the highest shoot concentration was slightly lower than the value of 475 mg kg À 1 that was found to be the shoot concentration above which manganese toxicity was deemed to have started in a study of 30-day wheat seedlings in hydroponic culture. [28] Fresco, the cultivar that was less affected by salinity, contained higher concentrations of Mn on a dry mass basis at most rates of salt supply, although for both cultivars the plants that grew best (those with low rates of NaCl supply) tended to have lower concentrations of Mn in shoots and roots than the other plants. If Mn concentrations are related to plant growth, Fresco must have a higher threshold of tolerance to the element than Hussar.…”
Section: Marcel Dekker Inc • 270 Madison Avenue • New York Ny 10016mentioning
confidence: 95%